Penguatan Komunikasi Efektif : Pengabdian Masyarakat dalam Pengembangan Keterampilan Public Speaking Guru dan Instruktur di Pondok Pesantren - Asep Soegiarto; Wina Puspita Sari; Abdul Kholik; Anggun Nadia Fatimah; Afina Damayanti; Sulthan Arrafi Fadhila (ARDHI : Jurnal Pengabdian Dalam Negri, 2024)
Effective communication is a crucial skill for educators, particularly in religious institutions like Pondok Pesantren. This community service project aimed to enhance the public speaking abilities of teachers and instructors at a Pondok Pesantren. Through interactive workshops and practical exercises, participants were trained in various aspects of public speaking, including voice modulation, body language, content organization, and audience engagement. The project emphasized the importance of clear and confident communication in imparting knowledge and religious teachings. Pre- and post-training evaluations showed significant improvements in the participants' public speaking skills, confidence levels, and teaching effectiveness. The project's success highlights the value of community service initiatives in promoting professional development and fostering a conducive learning environment within religious educational institutions